Manhaj Taʿlīm al-Lughah al-ʿArabiyyah li al-Nāṭiqīn bi Ghayrihā (Dirāsah Waṣfiyyah li al-Dawrah al-Tadrībiyyah al-Mukaththafah fī al-Lughah al-ʿArabiyyah bi Markaz al-Lughah, Jāmiʿat Dār al-Salām Gontor) - Alif Cahya Setiyadi; Agung Prawoto (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
The Arabic language training program organized by the Language Center of Universitas Darussalam Gontor is an intensive educational initiative designed to develop learners’ proficiency in the four essential language skills: speaking, listening, reading, and writing. The program provides a comprehensive set of language activities supported by a curriculum specifically designed to achieve its instructional objectives. Arabic instruction in this program follows an integrated curriculum that combines classroom learning with extracurricular language activities to create a continuous Arabic-speaking environment throughout the day. Consequently, the instructional approaches employed inside the classroom differ from those implemented outside the classroom in order to maximize language exposure and communicative practice. This study provides a detailed descriptive analysis of the instructional curriculum used in the intensive Arabic training program at the Language Center of Universitas Darussalam Gontor. It examines the curriculum design as well as the teaching methods and instructional techniques applied in delivering the program's learning materials.